Eksplorasi Etnomatematika pada Bangunan Cagar Budaya Ukiran Relief Istana Maimun di Kota Medan - Mailani, Elvi; Saragih, Doni Irawan; Mardayanti, Fitri; Sitorus, Septi Qorima; Capah, Aribah; Indah T, Khofifah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Ethnomathematics is a field of study that combines mathematical concepts with cultural elements in people's lives. Maimun Palace, as one of the Malay cultural heritages located in Medan, North Sumatra, offers many examples of the application of ethnomathematics in its architecture and design. This research aims to explore how mathematical concepts, such as geometry, symmetry, fractals and proportions, are implemented in the building structure, ornaments and spatial layout of the Maimun Palace. The palace's architecture reflects a blend of local Malay, Islamic, Indian and European cultural influences, each of which carries unique mathematical values. In addition, symbolic elements of certain numbers are also found in the palace design, reflecting the cultural beliefs and philosophies of the local people. The results of this research show that the Maimun Palace is an important example of how mathematics is not only applied in a technical context, but is also influenced by beliefs, aesthetics, and cultural traditions. This study contributes to increasing understanding of the relationship between mathematics and culture and the importance of preserving cultural heritage through a multidisciplinary approach such as ethnomathematics. The method used is qualitative using library research